Red Nucleus Interleukin-6 Evokes Tactile Allodynia in Male Rats Through Modulating Spinal Pro-inflammatory and Anti-inflammatory Cytokines - Yang, Qing-Qing; Li, Hao-Nan; Xia, Yu-Tong; Tian, Xue; Feng, Fan; Yang, Jian; Xu, Ya-Li; Guo, Juan; Li, Xiao-Qi; Wang, Jun-Yang; Zeng, Xiao-Yan (Frontiers in Molecular Neuroscience, 2022)
Our previous studies have clarified that red nucleus (RN) IL-6 is involved in the maintenance of neuropathic pain and produces facilitatory effect by activating JAK2/STAT3 and ERK pathways. Here, we further explored the immune molecular mechanisms of rubral IL-6-mediated descending facilitation at the spinal cord level. IL-6-evoked tactile allodynia was established by injecting recombinant IL-6 into the unilateral RN of naive male rats. Following intrarubral administration of IL-6, an obvious tactile allodynia was evoked in the contralateral hindpaw of rats. Meanwhile, the expressions of pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were elevated in the contralateral spinal dorsal horn (L4 - L6), blocking spinal TNF-α, IL-1β or IL-6 with neutralizing antibodies relieved IL-6-evoked tactile allodynia. Conversely, the levels of anti-inflammatory cytokines TGF-β and IL-10 were reduced in the contralateral spinal dorsal horn (L4 - L6), intrathecal supplement of exogenous TGF-β or IL-10 attenuated IL-6-evoked tactile allodynia. Further studies demonstrated that intrarubral pretreatment with JAK2/STAT3 inhibitor AG490 suppressed the elevations of spinal TNF-α, IL-1β and IL-6 and promoted the expressions of TGF-β and IL-10 in IL-6-evoked tactile allodynia rats. However, intrarubral pretreatment with ERK inhibitor PD98059 only restrained the increase of spinal TNF-α and enhanced the expression of spinal IL-10. These findings imply that rubral IL-6 plays descending facilitation and produces algesic effect through upregulating the expressions of spinal pro-inflammatory cytokines TNF-α, IL-1β, IL-6 and downregulating the expressions of spinal anti-inflammatory cytokines TGF-β and IL-10 by activating JAK2/STAT3 and/or ERK pathways, which provides potential therapy targets for the treatment of pathologic pain.